A study of vibration-control design parameters using models with two degrees of freedom - Andalecio, Melinda N. (2001)
This thesis studies the optimum condition of design parameters in vibration control problems analyzed as two-mass model. The conclusions from this model will serve as guide for initial selection of design parameters for the vibration control system. The three problems considered are tuned mass damper (TMD) system, machine isolation (MI) system, and base isolation (BI) system. The thesis presents: the selection of examples of 2DOF (two-degree-of-freedom) problems with their corresponding practical range of parameters; the design criteria; and procedures implemented in Mathcad2000 software. Three design criteria for each problem are formulated and adapted based on relevance and usefulness in civil engineering. Parametric studies have been conducted to investigate the effect design variables. Results are presented trough tables and figures for many combinations of design parameters. Most cases consider harmonic excitation; but the study also extends to such simple periodic excitations as rectangular wave, or triangular or sawtooth. To calculate the dynamic response of two-degree-of-freedom problems with varying parameters, a technical tool has been developed through implementation of algorithms in Mathcad2000; the program is called "2DOF".